Effect Of Eccentric Training And Isolytic Contraction To Improve Flexibility Of Quadriceps In Recreational Marathoners.: Life Sciences-Physiotherapy - Sharvari .D. Wagh; Dr. Namrata Kadam (International Journal of Life Science and Pharma Research, 2022)
In the field of athletics, running is one of the most popular activities having beneficial health effects as well as negative effects during sports injury. Not only elite marathoners, but recreational marathoners have various lower limb musculoskeletal injuries that occur quite frequently which produces an adverse effect over the performance of the marathoners. Studies have suggested that the most common muscles that were affected were quadriceps group of muscles as well as the hamstrings muscles. The main mechanism behind the injury to the quadriceps muscles is the strong contraction of the muscle against the forced flexion action of the knee joint which is commonly seen in runners in a downhill marathon. Some of the risk factors that are responsible for the quadriceps muscle strains are inadequate stretching, muscle imbalance of the lower extremity and inadequate warm-up before vigorous exercise. Objective of this study was to find out the effect of eccentric training and whether isolytic contraction helps to improve the flexibility of the quadriceps muscle and joint range of motion of knee as well as hip joint. A total of 30 subjects were selected for the study from Krishna College of Physiotherapy. The subjects were divided into two groups namely, group A and group B consisting of 15 subjects each. Demographic data, assent and consent was taken from the marathoners that were selected according to the inclusion criteria. Pre and post assessment was taken on the basis of both active range of motion of the hip joint, active range of motion of knee joint, Manual Muscle Test of the quadriceps and Ely’s test for quadriceps before and after 6 weeks (total 16 sessions) of the treatment respectively. The session lasted for a time period of 45 mins. After the data was collected, evaluation and interpretation of collected data was done thoroughly. The subjects under the eccentric training protocol were found to have more effect compared to the ones in the group consisting of isolytic contraction protocol. The conclusion of this study was that significant effect of eccentric training and isolytic contraction helps to improve the flexibility of the quadriceps muscle and joint range of motion.